KARAKTERISTIK GAS-GAS HASIL PIROLISIS TANDAN KOSONG KELAPA SAWIT - Agus S Ginting, Armansyah H Tambunan dan Radite P A Setiawan (Jurnal Teknologi Industri Pertanian, 2015)
Palm empty fruit bunches is about of 23% of total fresh fruit bunches, which are rich in lignocellulosic(cellulose, hemycellulose and lignin) content. The bunches can be converted into flammable gases (H2, CO andCH4) by pyrolysis. The objective of this research was to characterize gases produced from palm empty fruitbunch pyrolisis using a laboratory scale reactor with capacity of 152.9 g. The pyrolysis temperature was set at200oC, 250oC, 300oC, 350oC, 400oC and 450oC. The results showed an increase in the mass fraction of H2 andCH4 gas, but decrease of CO gas, by increasing pyrolysis temperature. The highest caloric value of gas wasobtained at temperature of 450oC, which was 6,7682 kJ/g. The result also showed that pyrolysis of empty fruitbunches should be at temperature of 250oC or higher to obtain the flammable gas.Keywords: empty fruit bunches, pyrolysis, flammable gas